Proceso de atención de enfermería en recién nacido con síndrome de Apert - Zapata Salvatierra, Sofía Galilea (2021)
Apert syndrome is a genetic anomaly, characterized by the triad of craniosynostosis, syndactyly in the hands and feet, along with a series of dysmorphic features. In the following clinical case, a newborn is diagnosed with Apert syndrome in the neonatology area. An investigation was conducted into Apert syndrome, its causes and complications. An evaluation of the patient, and an evaluation by functional patterns, is performed to be able to perform a nursing care process that is coupled to the patient’s needs. The nursing care process will be carried out using the taxonomies NANDA (diagnostics), NOC (results), NIC (interventions), in order to ensure quality care, and to meet the goals and objectives established in this case study.